2021
DOI: 10.1021/acs.langmuir.1c01745
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of the Turbulent Boundary Layer for Biomimetic Protrusive Surfaces Inspired by Pufferfish Skin: Effects of Spinal Density and Diameter

Abstract: Pufferfish is known for its extension of tiny spinecovered skin that appears to increase skin drag and may act as turbulisors, reducing overall drag while serving a protective function. Therefore, the present study addresses a neglected aspect of how spines affect the turbulent boundary layer (TBL) for drag reduction in the pufferfish skin. Particle image velocimetry (PIV) was utilized to investigate the TBL structure on the biomimetic spine-covered protrusion samples inspired by the back skin of the pufferfis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…However, the two-point correlation coefficient contours between the biomimetic surface CPES and the smooth surface CS are relatively significant. However, compared with the samples with the same protrusion CPRS is smaller, which is consistent with the previous work . This indicates that the drag reduction performance is not only positively related to the regular protrusion structure formation but also to the elastic layer coated on the surface.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…However, the two-point correlation coefficient contours between the biomimetic surface CPES and the smooth surface CS are relatively significant. However, compared with the samples with the same protrusion CPRS is smaller, which is consistent with the previous work . This indicates that the drag reduction performance is not only positively related to the regular protrusion structure formation but also to the elastic layer coated on the surface.…”
Section: Resultssupporting
confidence: 91%
“…The experimental test data are taken under the stable flow rate of the test system, and the experimental error can be guaranteed to be less than 2% under all sample experimental tests. Additionally, more details about the PIV experiment can be found in our previous work …”
Section: Methods and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 The special spine-like structure on the body surface of puffer fish can effectively delay the separation of turbulent boundary layers. 13 Muthuramalingam et al studied the DR performance of European sea bass scales and found that the alternating high and low-speed stripes generated by scales in the near-wall region could reduce the drag. 14 Chen et al investigated the coupling DR function of tuna scales and flexible body surface, and the maximum DR rate reached 25.7% due to the vortexes effect of flexible epidermis.…”
Section: Introductionmentioning
confidence: 99%